2020
DOI: 10.1002/jcu.22855
|View full text |Cite
|
Sign up to set email alerts
|

Are increased left ventricular strains compensatory effects in lipedema? Detailed analysis from the three‐dimensional speckle‐tracking echocardiographic MAGYAR‐Path Study

Abstract: Purpose Lipedema is a chronic, common but underdiagnosed disease masquerading obesity, with female predominance, characterized by disproportional abnormal adipose tissue distribution of the lower and also upper extremities. The present study was designed to determine whether lipedema is associated with three‐dimensional (3D) speckle‐tracking echocardiography (3DSTE)‐derived left ventricular (LV) deformation abnormalities, and to assess the effects of 1‐hour use of medical compression stockings (MCS). Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The diameter of the left ventricle in the control group was 45.8 ± 3.2 mm, and in the study group it was 49.8 ± 3.2 mm. The ejection fraction in the control group was 64.3 ± 4.3%, and in the study group it was 68.3 ± 3.6% [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of the left ventricle in the control group was 45.8 ± 3.2 mm, and in the study group it was 49.8 ± 3.2 mm. The ejection fraction in the control group was 64.3 ± 4.3%, and in the study group it was 68.3 ± 3.6% [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The research was conducted using PRISMA methodotogy (Figure 1) The review was conducted according to the PRISMA method and it distinguished 10 papers, which are presented in Table 1. Qualitative research • Subjective self-evaluation of the impact of lipoedema on health [28] Case study • Lipoedema and eating disorders [29] Pilot study • The connection between pain and psychological stress in people with lipoedema [20] Other study • Lipoedema comorbidities [30] • Left atrial and ventricular abnormalities in people with lipoedema [31] 3. Results…”
Section: Methodsmentioning
confidence: 99%
“…Early detection of changes in LV volumetric and functional abnormalities could help in selecting patients with increased risk. In recent studies, diagnostic and prognostic impact of LV deformation have been demonstrated in several disorders (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). LV has a special 3D movement respecting the cardiac cycle as well due to its special helical 3D structure.…”
Section: Discussionmentioning
confidence: 99%
“…In total, twenty-seven cross-sectional studies [15,16,, ten cohorts [61][62][63][64][65][66][67][68][69][70], three randomized controlled trials [71][72][73], four controlled clinical trials [74][75][76][77], one clinical trial [78], five case report studies [6,[79][80][81][82], and one qualitative study [83] were included. Two studies used a cross-sectional and a cohort design to answer the research questions [84,85]. Two non-peer-reviewed studies were included in this review.…”
Section: Study Characteristicsmentioning
confidence: 99%